Performance Analysis of VoIP in Multi-Hop Wireless Network - Rahmat, Mohamad Faris; Idris, Fakrulradzi; Mohd Nizam, Mohd Zul Azri; Sarimin, Nuraishah; Mohamad, Mas Haslinda (2012)
This paper presents the performance evaluation of Voice over Internet Protocol (VoIP) in Multi-hop Wireless Network (MWN) developed using Multi-radio Access Relay (MAR). The MWN is deployed using 3 MARs in Universiti Teknikal Malaysia campus. The performance of VoIP are investigated using Real Time Protocol (RTP) and Compress Real Time Protocol (CRTP) header techniques. RTP and CRTP are used to transport voice packets using G711.1, G723.1 and G729.2 codec. The performance of VoIP is analyzed based on three important elements which are delay, jitter and packet loss.